“Nobody Knows Anything about These Men who has not Seen them in Battle”: Reclaiming the Slaves’ Bravery through Emancipation Narratives - Gimeno Pahissa, Laura (Estudios Ingleses de la Universidad Complutense, 2010)
This paper discusses the work of Susie King Taylor, an African American nurse and teacher who wrote her memoirs after the American Civil War. Her text—Reminiscences of My Life in Camp with the 33d United States Colored Troops, Late 1st South Carolina Volunteers (1905)—constitutes a remarkable example of a “postbellum slave narrative” or “emancipation narrative”3, a transitional genre emerging from the armed conflict which lasted well into the first two decades of the twentieth century. Texts such as Taylor’s have largely been forgotten by scholars, but are central to understanding the tensions experienced by black Americans in the late nineteenth century, and how they faced new challenges, such as their interpretation of and involvement in the armed conflict; whether adjustment and submission were the only solutions left for blacks; what concessions they had to make to become part of American society; and how they were to narrate their experience of liberation, war and its aftermath.